On-line hybrid test combining with general-purpose finite element software. - Wang, Tao
A new on-line hybrid test system incorporated with the substructuring technique is developed. In this system, a general-purpose finite element software is employed to obtain the restoring forces of the numerical substructure accurately. The restart option is repeatedly used to accommodate the software with alternating loading and analysis characteristic of the on-line test but without touching the source code. An eight-storey base-isolated structure is tested to evaluate the feasibility and effectiveness of the proposed test system. The overall structure is divided into two substructures, i.e. a superstructure to be analysed by the software and a base-isolation layer to be tested physically. Collisions between the base-isolation layer and the surrounding walls are considered in the test. The responses of the overall structure are reasonable, and smooth operation is achieved without any malfunction.
Keywords: On-line hybrid test; Substructuring; ABAQUS; Restart; Base isolation; Collision